An overview of biofuel power generation on policies and finance environment, applied biofuels, device and performance - Yang Yang; Zhilin Tian; Yuanfeng Lan; Shu Wang; Hao Chen (Journal of Traffic and Transportation Engineering (English ed. Online), 2021)
The prices of fossil fuels, the gap between energy supply and demand, energy security, environmental issues, and the reduction of greenhouse gas emissions commonly promote the development of biomass power generation in China. Compared to direct biomass combustion power generation and biogas power generation, liquid biofuel power generation has better application potential. Policies and finance environment of countries and organizations have promoted the extensive application of biofuel power generation in recent years, especially in China. Evaluation of internal combustion engine, gas turbine and fuel cell on the stationary power station and mobile generation shows that gas turbine is the main generator-set, the fuel cell is the fastest-growing and future generator-set, while the engine is the first choice in transport and low power generation field. As the second, third and fourth generation biofuels, biomethanol, bioethanol, biodiesel and others have been researched and widely used in power generation. In addition, power generation performance and emissions have been improved to some extent after biofuels supplying. For the future, combined heat and power (CHP) generation and integrated gasification combined cycle (IGCC) is imperative development trends of power generation for higher energy and exergy efficiency. CHP based on the various generating facilities will be the next choice and direction of energy use trends for transport.